2019
DOI: 10.1111/epi.16284
|View full text |Cite
|
Sign up to set email alerts
|

Increased electroencephalography connectivity precedes epileptic spasm onset in infants with tuberous sclerosis complex

Abstract: Objective To identify whether abnormal electroencephalography (EEG) connectivity is present before the onset of epileptic spasms (ES) in infants with tuberous sclerosis complex (TSC). Methods Scalp EEG recordings were collected prospectively in infants diagnosed with TSC in the first year of life. This study compared the earliest recorded EEG from infants prior to ES onset (n = 16) and from infants who did not develop ES (n = 28). Five minutes of stage II or quiet sleep was clipped and filtered into canonical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 45 publications
7
25
0
Order By: Relevance
“…Even though research on generalized epilepsy, explicitly, epileptic encephalopathy is very limited in the literature, our results are in agreement with other findings in genetic generalized epilepsy, which have shown a general increase in connectivity manifested in all aspects of network analyses (Ponten et al, 2009 ; Niso et al, 2015 ; Davis et al, 2019 ). In this study, an overconnectivity for all bands, except for the alpha band was also detected in patients with epileptic encephalopathy.…”
Section: Discussionsupporting
confidence: 93%
“…Even though research on generalized epilepsy, explicitly, epileptic encephalopathy is very limited in the literature, our results are in agreement with other findings in genetic generalized epilepsy, which have shown a general increase in connectivity manifested in all aspects of network analyses (Ponten et al, 2009 ; Niso et al, 2015 ; Davis et al, 2019 ). In this study, an overconnectivity for all bands, except for the alpha band was also detected in patients with epileptic encephalopathy.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are broadly consistent with EEG data in children harboring Tsc2 mutations, in which increased inter-regional neural coherence has been reported (Davis et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…The finding of increased network efficiency during IEDs and in their absence is supported by simultaneous EEG-fMRI studies that showed similar epileptic network patterns during IEDs and in their absence ( Iannotti et al, 2016 ). In other epileptic conditions, increased efficiency in infants with tuberous sclerosis was found to be predictive of the subsequent occurrence of epileptic spasms, therefore also suggesting more widespread epileptic networks ( Davis et al, 2019 ). In Benign Epilepsy with Centro-Temporal Spikes (BECTS) results are more difficult to interpret, due to heterogeneity of EEG analysis strategies ( Adebimpe et al, 2016 , Ji et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%